ENHANCING THE SKILLS ENHANCEMENT OF HYDROCARBON BY GUIDED CYCLE 3E LEARNING MODEL - Ika Eni Fadlin; Ratu Betta Rudibyani; Emmawaty Sofya (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This research aimed to describe the LC 3E learning model effectiviness in improving the communication skills of students in the subject matter of hydrocarbons.  The samples in this study were students of SMAN 7 Bandar Lampung class X4 and X5  Academic Year 2011-2012 Even Half that taken by porposive sampling technique.  This research was a quasi-experimental research design Non Equivalent (Pretest-Posttest) Control Group Design.  Hypothesis test used is the t-test.  Based on the result of the study, found that the avarage N-gain communication skills using learning model LC 3E is higher than that using conventional learning.  This implies that the  LC 3E learning model effective in improving student’s communication skills in the subject matter of hydrocarbons.Keyword: LC 3E models, communication skills, and effectiviness